Muscle cyclo-oxygenase-2 pathway contributes to the exaggerated muscle mechanoreflex in rats with congestive heart failure - Morales, Ariel (2012)
Cyclo-oxygenase (COX) enzymes are responsible for the formation from arachidonic acid of prostaglandins, among other metabolites. Prior studies have suggested that inhibition of the COX pathway attenuates the responses of sympathetic nerve activity and blood pressure during static muscle contraction. Static muscle contraction activates the exercise pressor reflex, which in turn increases sympathetic nerve activity and blood pressure. Also, COX products contribute to exaggeration of the exercise pressor reflex in heart failure (HF). This dysfunction of the exercise pressor reflex has previously been shown to be mediated primarily by muscle mechanoreflex overactivity. It is well known that COX-1 and COX-2 are two isoforms of the enzyme that lead to formation of these important biological mediators involved in the muscle reflex. Thus, in the present study, we determined whether the COX-1 and/or COX-2 pathway contribute(s) to the augmented mechanoreflex activity in HF. First, Western blot analysis was employed to examine protein expression of COX-1 and COX-2 in skeletal muscle tissue of control rats and rats with HF induced by myocardial infarction. Our data show that there is no significant difference in COX-1 expression in both experimental groups. However, COX-2 displays significant overexpression in rats with HF compared with control rats (optical density 1.06 ± 0.05 in control and 1.6 ± 0.05 in HF, P < 0.05 versus control). Second, the mechanoreflex was evoked by passive tendon stretch, and the reflex sympathetic and pressor responses to muscle stretch were examined after COX-1 and COX-2 inhibitors (FR-122047 and SC-236) were individually injected into the arterial blood supply of the hindlimb muscles. The results demonstrate that the stretch-evoked reflex responses in rats with HF were significantly attenuated by administration of SC-236, but not by FR-122047, i.e. renal sympathetic nerve activity and mean arterial pressure responses evoked by 0.5 kg of muscle tension were 52.3 ± 8.9% and 19 ± 1.4 mmHg, respectively, in control conditions and 26.4 ± 5.6% and 5.7 ± 1.6 mmHg (P < 0.05 versus control group) after 0.25 mg kg(−1) of SC-236. Muscle stretch-evoked renal sympathetic nerve activity and mean arterial pressure responses were 51.8 ± 8.2% and 18.7 ± 1.2 mmHg, respectively, in control conditions and 48.3 ± 5.3% and 17.5 ± 1.9 mmHg (P > 0.05 versus control group) after 1.0 mg kg(−1) of FR-122047. Accordingly, the results obtained from this study support our hypothesis that heightened COX-2 expression within the hindlimb muscles contributes to the exaggerated muscle mechanoreflex in congestive HF.